On the existence and function of galanin receptor heteromers in the central nervous system - Fuxe, Kjell; Borroto-Escuela, Dasiel O.; Romero-Fernandez, Wilber; Tarakanov, Alexander O.; Calvo, Feliciano; Garriga, Pere; Tena, Mercé; Narvaez, Manuel; Millón, Carmelo; Parrado, Concepción; Ciruela, Francisco; Agnati, Luigi F.; et al. (Frontiers in Endocrinology, 2012)
Galanin receptor (GalR) subtypes 1–3 linked to central galanin neurons may form heteromers with each other and other types of G protein-coupled receptors in the central nervous system (CNS). These heteromers may be one molecular mechanism for galanin peptides and their N-terminal fragments (gal 1-15) to modulate the function of different types of glia–neuronal networks in the CNS, especially the emotional and the cardiovascular networks. GalR–5-HT1A heteromers likely exist with antagonistic GalR–5-HT1A receptor–receptor interactions in the ascending midbrain raphe 5-HT neuron systems and their target regions. They represent a novel target for antidepressant drugs. Evidence is given for the existence of GalR1–5-HT1A heteromers in cellular models with trans-inhibition of the protomer signaling. A GalR1–GalR2 heteromer is proposed to be a galanin N-terminal fragment preferring receptor (1-15) in the CNS. Furthermore, a GalR1–GalR2–5-HT1A heterotrimer is postulated to explain why only galanin (1-15) but not galanin (1-29) can antagonistically modulate the 5-HT1A receptors in the dorsal hippocampus rich in gal fragment binding sites. The results underline a putative role of different types of GalR–5-HT1A heteroreceptor complexes in depression. GalR antagonists may also have therapeutic actions in depression by blocking the antagonistic GalR–NPYY1 receptor interactions in putative GalR–NPYY1 receptor heteromers in the CNS resulting in increases in NPYY1 transmission and antidepressant effects. In contrast the galanin fragment receptor (a postulated GalR1–GalR2 heteromer) appears to be linked to the NPYY2 receptor enhancing the affinity of the NPYY2 binding sites in a putative GalR1–GalR2–NPYY2 heterotrimer. Finally, putative GalR–α2-adrenoreceptor heteromers with antagonistic receptor–receptor interactions may be a widespread mechanism in the CNS for integration of galanin and noradrenaline signals also of likely relevance for depression.